Do patients treated for colorectal cancer benefit from general practitioner support? A video vignette study - Ngune, I.; Jiwa, M.; McManus, Alexandra; Parsons, Richard; Pagey, G.; Hodder, R. (2015)
Background: Patients who have been treated for colorectal cancer in Australia can consult their general practitioner (GP) for advice about symptoms or side effects at any time following their treatment. However, there is no evidence that such patients are consistently advised by GPs, and patients experience substantial unmet need for reassurance and advice. Objective: To explore the patient management options selected by GPs to treat a set of patients describing their symptoms following treatment for colorectal cancer. Methods: This was an Internet-based survey. Participants (GPs) viewed 6 video vignettes of actors representing patients who had been treated for colorectal cancer. The actor-patients presented problems that resulted from their treatment. Participants indicated their diagnosis and stated if they would prescribe, refer, or order tests, based on that diagnosis. These responses were then rated against the management decisions for those vignettes as recommended by a team of colorectal cancer experts. Results: In total, 52 GPs consented to take part in the study, and 40 (77%) completed the study. Most GPs made a diagnosis of colorectal cancer treatment side effects/symptoms of recurrence that was consistent with the experts' opinions. However, correct diagnosis was dependent on the type of case viewed. Compared with radiation proctitis, GPs were more likely to recognize peripheral neuropathy (odds ratio, OR, 4.43, 95% CI 1.41-13.96, P=.011) and erectile dysfunction (OR 9.70, 95% CI 2.48-38.03, P=.001), but less likely to identify chemotherapy-induced fatigue (OR 0.19, 95% CI 0.08-0.44). GPs who had more hours of direct patient care (OR 0.38, 95% CI 0.17-0.84, P=.02), were experienced (OR 9.78, 95% CI 1.18-8.84, P=.02), and consulted more patients per week (OR 2.48, 95% CI 1.16-5.30, P=.02) suggested a management plan that was consistent with the expert opinion. Conclusions: In this pilot study, years of experience and direct patient contact hours had a significant and positive impact on the management of patients. This study also showed promising results indicating that management of the common side effects of colorectal cancer treatment can be delegated to general practice. Such an intervention could support the application of shared models of care. However, a larger study, including the management of side effects in real patients, needs to be conducted before this can be safely recommended.